Choice, preferences, and procedures : a rational choice theoretic approach - Suzumura, Kōtarō, 1944-2020 (Harvard University Press, 2016)
"Social choice theory critically assesses and rationally designs economic mechanisms for improving human well-being. Kotaro Suzumura-- one of the world's foremost thinkers in social choice theory and welfare economics--fuses abstract ideas with real-world economies to examine foundational issues of normative economics and collective decision-making"--Provided by publisher